1999
DOI: 10.1590/s0004-282x1999000100004
|View full text |Cite
|
Sign up to set email alerts
|

Sustained long-term improvement with clozapine in schizophrenia

Abstract: SUMMARY -The present paper reports the long-term use of clozapine in a prospective sample of 46 chronic schizophrenics. In six months, 21 subjects had been excluded for a number of reasons. In four of them the reasons for exclusion were related to lack of response or adverse effects. The median daily clozapine dose was 400 mg in the remaining 25 patients. As a whole, there were remarkable improvements in core dimensions of psychopathology, global cognitive status, and level of functioning. We confirmed that cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In a previous article we reported our experience with the first 6 months of treatment of schizophrenia using clozapine. 4 The results of this earlier study were in strong agreement with those involving larger series of patients. For example, one of the first studies on the time for clozapine response in a series of 50 patients with refractory schizophrenia showed that those who eventually improved, i.e., 68% of patients, did so within the first 8 weeks of treatment.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…In a previous article we reported our experience with the first 6 months of treatment of schizophrenia using clozapine. 4 The results of this earlier study were in strong agreement with those involving larger series of patients. For example, one of the first studies on the time for clozapine response in a series of 50 patients with refractory schizophrenia showed that those who eventually improved, i.e., 68% of patients, did so within the first 8 weeks of treatment.…”
supporting
confidence: 85%
“…Previous work by the authors 4 and others 18 , 19 has indicated that clozapine promotes a noticeable improvement in patients with severe schizophrenia by the end of 6-12 months. The present investigation further indicates that, following this initial response, an enduring period of clinical stability ensues which does not seem to appreciably change in the long-term ( Figure ).…”
Section: Discussionmentioning
confidence: 88%
“…Despite these safety concerns, studies have reported that clozapine is associated with a decreased mortality risk, compared with other antipsychotics (Hayes et al, 2014; Wimberley et al, 2017). There are also corresponding improvements in symptoms and functioning (De Oliveira-Souza et al, 1999; Wahlbeck et al, 2009), which are the ideal measures of assessing the efficacy of clozapine, in accordance to usual clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The main neuropsychological pattern is characterized by impairments in attention, executive performance, learning and memory with relative sparing of verbal knowledge and complex visual perception. 32 Major challenges for future studies include (i) a better understanding of the patterns of dementia and cognitive impairments in schizophrenia, 43 and (ii) how they relate to psychopathological status, (iii) how they adversely affect socio-occupational functioning, (iv) how they may differentially respond to pharmacological and cognitive-behavioral treatment, 44 and (v) how schizophrenia can improve our understanding about the cerebral organization presiding the human mind and behavior. 45 …”
Section: The Concept Of Schizophrenia: a Brief Overviewmentioning
confidence: 99%